Trajectory following sliding mode control of induction motors - Akpolat, ZH; Guldemir, H (Springer-Verlag, 2003)
In this paper, a discrete-time control scheme based on a trajectory following structure and the reaching law control method, which is an approach to sliding mode control design, is described for the speed control of induction motor drives. The simulation and experimental results showing the effectiveness of the proposed control scheme are presented. The experimental results are obtained from a test-rig implemented for research and educational purposes.
Keywords: sliding mode control; reaching law; electrical drives; control; induction motors